Improved mechanical properties of carbon ﬁber reinforced PTFE composites by growing graphene oxide on carbon ﬁber surface. Issue 11 (2nd November 2018) - He, Runqin; Chang, Qiuxiang; Huang, Xinjun; bo, Jin
Abstract: The mechanical properties of carbon fiber reinforced polymer composites depend upon fiber-matrix interfacial properties. To improve the mechanical properties of ﬁbers/PTFE composites without sacriﬁcing tensile strength of ﬁbers, graphene oxide (GO) was introduced onto the surface of CFs by chemical vapour deposition (CVD). This hybrid coating increased the wettability and surface roughness of carbon fibers, which led to improved affinity between the carbon fibers and PTFE matrix. The resulting hybrid-coated carbon fiber-reinforced composites showed an enhancement in the short beam strength compared to un-coated carbon fiber composites. Meanwhile, a signiﬁcant increase of interlaminar shear strength (ILSS), interface shear strength tests (IFSS) and impact property were achieved in the 5-min-modiﬁed CFs. Abstract : AFM images of CF surfaces: (a, d) untreated CF, (b, e) CF-5 min and (c, f) CF-10 min.